ESTIMATING THE IMPACT OF THE COUNTRY’S FINANCIAL STABILITY ON FOREIGN DIRECT INVESTMENT INFLOWS - Маханець, Любов (SWorldJournal, 2023)
It is shown that the Ukrainian government has repeatedly stated its intention to significantly increase foreign investment flows in the domestic economy. Now, in a time of war, raising additional funds is a matter of the state’s survival. Today, when the